Integrated Dissemination System of Frequency, Time and Data for Radio Astronomy - Yufeng Chen; Bo Wang; Lijun Wang; Keith Grainge; Richard Oberland; Richard Whitaker; Althea Wilkinson (IEEE Photonics Journal)
For radio telescope array applications, the precise time and frequency reference predominantly determines the quality of the observation. In this paper, we demonstrate an integrated dissemination system which can achieve ultra-stable frequency dissemination, time synchronization and data transfer simultaneously over a single optical fiber link. The test of this integrated system was carried out on the 48-km fiber link, which consisted of 28-km buried fibers, and 20-km fiber spool in laboratory. It has been experimentally demonstrated that the frequency transfer stability is $2.6 × {10^{ - 14}}/s$ and $3.0 × {10^{ - 16}}/{10^4}s$ . The time synchronization with 100-ps accuracy and the error bit ratio of data transfer at the level of 10-8 are also demonstrated.